Butanediol Conversion to Gamma‐Hydroxybutyrate Markedly Reduced by the Alcohol Dehydrogenase Blocker Fomepizole. Issue 5 (8th January 2019) - Liakoni, Evangelia; Gugelmann, Hallam; Dempsey, Delia A.; Wiegand, Timothy J.; Havel, Christopher; Jacob, Peyton; Benowitz, Neal L.
Abstract : 1, 4‐Butanediol (BDO)—used as solvent and abused for its euphoric effects—is converted to gamma‐hydroxybutyrate (GHB) by the enzyme alcohol dehydrogenase. This double‐blind, placebo‐controlled crossover study with six healthy volunteers is the first to date investigating the role of the ADH inhibitor fomepizole (4‐methylpyrazole (4MP)) in moderating this conversion in humans. Participants received on two different days either intravenous placebo or 15 mg/kg 4MP followed by oral administration of 25 mg/kg BDO. Pretreatment with 4MP resulted in significantly higher BDO maximal plasma concentration ( P = 0.001) and area under the concentration‐time curve (AUC; P = 0.028), confirming that ADH is the primary pathway for the conversion of BDO to GHB in humans. With 4MP, the mean arterial pressure was significantly lower at 105 minutes compared to baseline ( P = 0.003), indicating that blood pressure lowering, observed not with a temporal relationship to 4MP administration but after the maximum BDO concentration was reached, may be an intrinsic effect of BDO.